2021
DOI: 10.9767/bcrec.16.3.10281.571-580
|View full text |Cite
|
Sign up to set email alerts
|

Study of Hydrolysis Process from Pineapple Leaf Fibers using Sulfuric Acid, Nitric Acid, and Bentonite Catalysts

Abstract: The hydrolysis process of pineapple leaf fibers has been carried out using sulfuric acid, nitric acid, bentonite catalyst, and activated bentonite catalyst. The sugar content of the hydrolysis product was identified using the phenol-sulfuric acid method by UV-Visible spectrophotometry. The disposal of pineapple leaf is a big problem even though it has high cellulose content (70–80%) and very promising to produce sugar by hydrolysis process. The purpose of this experiment was to determine the effectiveness of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Figure 4f shows the tensile strength of ZIF-67-CT was 25.98 MPa, ~ 17% lower than that of the pristine cotton textile CT (31.43 MPa), whereas the elongation was not changed. Besides, the tensile strength of CT-COOH was 26.28 MPa, similar to ZIF-67-CT (25.98 MPa), which is lower than that of the pristine cotton textile CT (31.43 MPa), demonstrating the decrease of the tensile strength of cotton fiber mainly caused by the acid solution treatment during the carboxymethylation of CT in HCl solution 46 . We further tested the flexural rigidity and air permeability performances of the CT, CT-COOH, and ZIF-67-CT samples.…”
Section: Resultsmentioning
confidence: 81%
“…Figure 4f shows the tensile strength of ZIF-67-CT was 25.98 MPa, ~ 17% lower than that of the pristine cotton textile CT (31.43 MPa), whereas the elongation was not changed. Besides, the tensile strength of CT-COOH was 26.28 MPa, similar to ZIF-67-CT (25.98 MPa), which is lower than that of the pristine cotton textile CT (31.43 MPa), demonstrating the decrease of the tensile strength of cotton fiber mainly caused by the acid solution treatment during the carboxymethylation of CT in HCl solution 46 . We further tested the flexural rigidity and air permeability performances of the CT, CT-COOH, and ZIF-67-CT samples.…”
Section: Resultsmentioning
confidence: 81%
“…Total sugar was analysed by using the phenol-sulphuric method [ 24 ]. The sugar type was analysed using High Performance Liquid Chromatography (HPLC) (Verti Sep TM GES, NH2 column; RID detector, Shimazu, Kyoto, Japan) with chromatographic conditions of 40 °C; 90:10 of acetonitrile; water; and 0.75 mL/min flow of mobile phase.…”
Section: Methodsmentioning
confidence: 99%
“…4 shows the glucose yield from rice husk after 60 minutes of hydrolysis reaction time using thermally catalyzed clays at 400 0 C, 600 0 C, and 900 0 C. In comparison to other catalyst doses at the same substrate dosage, the hydrolysis with 0.06g/30ml catalyst dosage at 200 0 C produced the maximum glucose yield. According to Prajitha and Pushpaletha [10] and Wiyantoko et al [19], 600 0 C thermal activated clay produced the highest glucose yield of 20.58%. For three ranges of catalyzed clays, it was shown that yield decreased with increasing catalyst doses above the catalyst dosage of 0.06g/30ml [17].…”
Section: Effect Of Catalyst Dosage With Thermally Activated Claymentioning
confidence: 99%
“…A clay catalyst with a 1-hour activation time produced the maximum glucose production during a 60-minute hydrolysis reaction time when used with a 0.04g/30ml catalyst dosage. According to Wiyantoko et al, [19] and McMillan [21], alkaline pretreatment to remove lignin can improve the hydrolysis of hemicelluloses without having a significant impact on other components. Additionally, unpretreated clay catalyst types produced the least amount of glucose, which supports the impact of clay pretreatment on rice husk hydrolysis.…”
Section: Effect Of Alkaline Activation Timementioning
confidence: 99%